Modifications In Turbo Coding System For Performance Enhancement - Balakrishnan, Bala Murali Thara (2005)
This thesis specifically describes the process of encoding and decoding turbo codes. A basic discussion of iterative decoding is presented. General turbo code performance issues are disccussed and observed through simulations. Two novel approaches to enhance the performance of turbo codes are proposed: a new modified turbo encoder and new unequal power allocation (UPA) scheme for 3G system.